Theoretical and methodological foundation of the process of students' physical training of higher educational institutions - Pilipej L. P. (Kharkov National Pedagogical University, 2013)
Efficiency of the existent system of physical education is considered in the higher institutes of Ukraine. Information of unsatisfactory level of physical preparedness of university entrants and graduating students of higher institutes is resulted. The lacks of construction of process of physical education are shown on the basis of normatively-command approach. Absence of the programs, which take into account motivation and terms of activity of higher institutes, disparity the requirements of integration in the river-bed of the Bologna Process, is shown. The analysis of publications is resulted in accordance with the modern scientific paradigm of construction of the system of physical education of students on the basis of methodology of synergetics. Information of the questionnaire questioning is utillized in research. Cross-correlation connections are presented between elements of physical education systems, which influence on efficiency of process. The basic requirements of construction of process of physical education of students of institutes of higher are set.